Community-based reconstruction of society : university involvement and lessons from East Japan compared with those from Kobe, Aceh, and Sichuan /: university involvement and lessons from East Japan compared with those from Kobe, Aceh, and Sichuan. ([2017]) - Unknown
No abstract available